Involvement of CD40-CD40L and ICOS-ICOSL in the development of chronic rhinosinusitis by targeting eosinophils - Zhou, Aina; Shi, Chenxi; Fan, Yuhui; Zheng, Yushuang; Wang, Jue; Liu, Zhichen; Xie, Huanxia; Liu, Jisheng; Jiao, Qingqing (Frontiers in Immunology, 2023)
Background: Chronic rhinosinusitis (CRS), whose prevalence and pathogenesis are age-related, is characterized by nasal tissue eosinophil infiltration. CD40-CD40 ligand (CD40L) pathway involves in the eosinophil-mediated inflammation, ICOS-ICOSL signal can strengthen CD40-CD40L interaction. Whether CD40-CD40L and ICOS-ICOSL have a role in the development of CRS remains unknown. Objectives: To investigate the association of CD40-CD40L and ICOS-ICOSL expression with CRS and underlying mechanisms. Methods: Immunohistology detected the expression of CD40, CD40L, ICOS, and ICOSL. Immunofluorescence was performed to evaluate the co-localizations of CD40 or ICOSL with eosinophils. Correlations between CD40-CD40L and ICOS-ICOSL as well as clinical parameters were analyzed. Flow cytometry was used to explore the activation of eosinophils by CD69 expression and the CD40 and ICOSL expression on eosinophils. Results: Compared with the Non-eCRS subset, ECRS (Eosinophilic chronic rhinosinusitis) subset showed significantly increased CD40, ICOS, and ICOSL expression. The CD40, CD40L, ICOS, and ICOSL expressions were all positively correlated with eosinophil infiltration in nasal tissues. CD40 and ICOSL were mainly expressed on eosinophils. ICOS expression was significantly correlated with the expression of CD40-CD40L, while ICOSL expression was correlated with CD40 expression. ICOS-ICOSL expression positively correlated with blood eosinophils count and disease severity. rhCD40L and rhICOS significantly enhanced the activation of eosinophils from ECRS patients. TNF-α and IL-5 obviously upregulated CD40 expression on eosinophils, which was significantly inhibited by the p38 MAPK inhibitor. Conclusions: Increased CD40-CD40L and ICOS-ICOSL expression in nasal polyps are linked to eosinophils infiltration and disease severity of CRS. CD40-CD40L and ICOS-ICOSL signals enhance eosinophils activation of ECRS. TNF-α and IL-5 regulate eosinophils function by increasing CD40 expression partly via p38 MAPK activation in CRS patients.